Comparison of CISS Score with Fixation Disparity as Measured with the Wesson Card. - Prestwich, Clinton; Cisarik, Patricia (Optometry & Visual Performance)
Background: Inclusion criteria for validation of the Convergence Insufficiency Symptom Survey (CISS) did not include fixation disparity (FD); thus, the relationship between CISS score and FD is unknown. This study compared FD and CISS score in a young, healthy graduate student population. Methods: Subjects (n=161) aged 22-42 years, with good acuity OU and no strabismus, completed the CISS and were evaluated for horizontal phoria and FD (Wesson card) at near. Subjects were separated by CISS score into HIGH (≽21) or LOW (<21) groups. Student t-test samples and one-way ANOVA were used for within- and between-group comparisons of mean FD and phoria. Results: Comparison of HIGH vs LOW CISS score groups showed no difference in magnitude of FD for any subgroup. Within the HIGH CISS score group, no difference in means was found for CISS score or magnitude of phoria among the 3 subgroups or for FD magnitude between eso and exo FD subgroups. Within the LOW CISS score group, no difference in means was found for CISS score or magnitude of phoria among the 3 subgroups; magnitude of FD was significantly different between eso and exo FD subgroups (p=0.005). Comparisons between HIGH and LOW groups for exo, eso, and no FD subgroups showed that mean CISS scores were significantly different for all subgroup comparisons (p<0.001); however, mean near phoria was different only for the exo FD subgroup (p=0.01). Conclusion: Neither the magnitude nor the direction of FD as measured with the Wesson card could be predicted by CISS score group.